Traumatic Brain Injury and Substance Related Disorder: A 10-Year Nationwide Cohort Study in Taiwan. (27th September 2016) - Wu, Chieh-Hsin; Tsai, Tai-Hsin; Su, Yu-Feng; Zhang, Zi-Hao; Liu, Wei; Wu, Ming-Kung; Chang, Chih-Hui; Kuo, Keng-Liang; Lu, Ying-Yi; Lin, Chih-Lung
Abstract : Whether traumatic brain injury (TBI) is causally related to substance related disorder (SRD) is still debatable, especially in persons with no history of mental disorders at the time of injury. This study analyzed data in the Taiwan National Health Insurance Research Database for 19, 109 patients aged ≥18 years who had been diagnosed with TBI during 2000–2010. An additional 19, 109 randomly selected age and gender matched patients without TBI (1 : 1 ratio) were enrolled in the control group. The relationship between TBI and SRD was estimated with Cox proportional hazard regression models. During the follow-up period, SRD developed in 340 patients in the TBI group and in 118 patients in the control group. After controlling for covariates, the overall incidence of SRD was 3.62-fold higher in the TBI group compared to the control group. Additionally, patients in the severe TBI subgroup were 9.01 times more likely to have SRD compared to controls. Notably, patients in the TBI group were prone to alcohol related disorders. The data in this study indicate that TBI is significantly associated with the subsequent risk of SRD. Physicians treating patients with TBI should be alert to this association to prevent the occurrence of adverse events.